Dampak Accounting Clinic Dalam Memproses Journal Entry - S, Suharyono (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study compares the test results before and after the accounting clinic was carried out. This study will prove whether the accounting clinic that has been attended by students can improve student competence in facing the certification exam. The population in this study were all first semester students of the D4 Public Finance Accounting Study Program Bengkalis State Polytechnic. The number of first semester students is 62 people. The entire population will be the object of this study. Based on the results of the clinical evaluation of accounting for group A, the average score showed a significant increase from the previous 85 to 92 or an increase of 7%. However, despite the increase in average scores, the pass rate has shown encouraging results. Of the 31 students in group A who attended the accounting clinic, only 4 failed. Whereas before attending the accounting clinic there were 8 students who failed. For the evaluation of the implementation of accounting clinics in group B, the average score increased from 83 to 91 or an increase of 8.7%. Meanwhile, the graduation rate achieved shows encouraging results. Of the 31 students who took the test, 24 people passed or were competent. While the number of students who failed as many as 7 people, decreased from the previous 12 students.